Some segmental features on the structure of the aortic wall of the dog - Orsi, A. M.; Stefanini, M. A.; Crocci, A. J.; Simoes, K.; Ribeiro, AACM (Blackwell Verlag Gmbh, 2004)
Structural features of segmental parts of the aorta of the dog were studied by light microscopy (LM) and scanning electron microscopy (SEM). The variability in the wall architecture composition and vascular thickness of the ascending (T2-3 level), thoracic (T7-8 level) and abdominal (L6-7 infrarenal level) segments of the aorta was analysed. Morphological features such as presence of intimal folds, pattern of the medial myoconnective components with segmental variations in the number of elastic lamellae, whose relative number was higher in the thoracic aorta (ascending and descending parts), compared with the abdominal aorta, and a network of connective (stromal) elements formed by elastic and collagen lamellae and fibres in the adventitia were observed. The results were discussed on a histophysiological basis, because small but significant segmental differences had been characterized in the aortic wall structure of the dog.